Perencanaan Kebutuhan Material Dengan Metode Material Requirement Planning - S Suhartini (Jurnal Teknik Industri, 2014)
Production activities which are conducted by some companies still use a lot of material inventory that production activities can run smoothly, but this condition is not considered optimal because many sources in the plant, so the investment is only in use for material. Ordering a material is not supported by data appropriately in product demand, it will make inventory of raw materials can not be sure so that the material is sometimes a lot and sometimes run out. The use of labor and production facilities are not accordance with demand, finally the production activities are not effective and efficient. Resources owned by the company must to be known in detail, so that the company can use capabilities of existing resources optimally. Company to achieve product demand should know the productive capacity, so that the ability of the company’s production targets can be achieved optimally, by measuring standard time at work operations and determine performance rating for each operator. In determining the demand for the product the next period using the method of linear regression forecasting the number of types of product demand of 1278 kg. Material requirements planning (MRP) orders can be made on day 7 of each month in accordance with the number of each type of raw material.